Ambivalence, the Intergroup Contact Hypothesis, and Attitudes about Gay Rights. Issue 2 (2nd April 2013) - Garner, Andrew
<x xml:space="preserve">Abstract</x> This article examines the effect of contact with gays and lesbians on inducing or decreasing ambivalence among citizens' attitudes toward gay rights. Contact may create cross‐pressure or ambivalence among strong conservative‐leaning citizens, causing internal conflict between their political values and their contact with gays and lesbians. Citizens torn between conflicting values will have less predictable attitudes than those not experiencing such conflict. Contact, however, is likely to have the opposite effect among liberal‐leaning citizens, reducing ambivalence and making their attitudes more predictable and uniform. Results from heteroskedastic regression models indicate that contact increases the error variance among evangelical Christians, strong conservatives, and strong Republicans while decreasing it among their liberal‐leaning counterparts. The results suggest that contact with gays and lesbians can impact the mean level of support for gay rights, as well as the clarity or certainty of those attitudes, although its effect differs across these two dimensions of public opinion. Related Articles <mixed-citation id="polp12010-cit-0054" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Bramlett</surname>, <given-names>Brittany H.</given-names></string-name> <year>2012</year>. " The Cross‐Pressures of Religion and Contact with Gays and Lesbians, and Their Impact on Same‐Sex Marriage Opinion ." <source content-type="journalTitle">Politics & Policy</source><volume>40</volume> (<issue>1</issue>): <fpage>13</fpage>‐<lpage>42</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2011.00337.x/full </mixed-citation> <mixed-citation id="polp12010-cit-0055" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Barth</surname>, <given-names>Jay L.</given-names></string-name>, and <string-name><given-names>Janine</given-names><surname>Parry</surname></string-name>. <year>2009</year>. " 2 > 1 + 1? The Impact of Contact with Gay and Lesbian Couples on Attitudes about Gays/Lesbians and Gay‐Related Policies ." <source content-type="journalTitle">Politics & Policy</source><volume>37</volume> (<issue>1</issue>): <fpage>31</fpage>‐<lpage>50</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2007.00160.x/abstract </mixed-citation> <mixed-citation id="polp12010-cit-0056" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Skipworth</surname>, <given-names>Sue</given-names></string-name> <string-name> <surname>Ann</surname>, <given-names>Andrew</given-names></string-name> <string-name> <surname>Garner</surname>, and <given-names>Bryan</given-names></string-name> <string-name> <surname>J. Dettrey</surname> </string-name>. <year>2010</year>. " Limitations of the Contact Hypothesis: Heterogeneity in the Contact Effect on Attitudes toward Gay Rights ." <source content-type="journalTitle">Politics & Policy</source><volume>38</volume> (<issue>5</issue>): <fpage>887</fpage>‐<lpage>906</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2010.00262.x/abstract </mixed-citation> Related Media <mixed-citation id="polp12010-cit-0057" publication-type="other" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <collab collab-type="groupName" xlink:type="simple">It Gets Better Project</collab>. <year>2010</year>. "<source content-type="otherTitle">What Is the It Gets Better Project</source>?" Accessed on December 20, 2012. Available online at http://www.itgetsbetter.org/pages/about‐it‐gets‐better‐project </mixed-citation> <mixed-citation id="polp12010-cit-0058" publication-type="other" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Edsall</surname>, <given-names>Thomas B.</given-names></string-name> <year>2012</year>. " Let the Nanotargeting Begin ." <source content-type="otherTitle">The New York Times</source> (April 15). http://campaignstops.blogs.nytimes.com/2012/04/15/let‐the‐nanotargeting‐begin </mixed-citation>